Q. 1 G4.1( 8 Votes )

<span lang="EN-US

Answer :

3x2 - 5x + 2 = 0

3x2 – 2x - 3x + 2 = 0


x(3x - 2) - 1(3x - 2) = 0


(x - 1) (3x - 2) = 0


The roots of the equation are those value for which (x - 1) (3x - 2) = 0



Hence are the roots of the given equation.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Introduction to Linear Equations in Two VariablesIntroduction to Linear Equations in Two VariablesIntroduction to Linear Equations in Two Variables62 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics